LAW ENFORCEMENT OF CONSTITUTIONAL COURT DECISION NO. 69/PUU -XII/2015 (Mixed Marriage Issue Without Marriage Agreement) - Any Suryani Hamzah; Mohammad Irfan (Warmadewa Press, 2018)
Abstrak The aims of this research is to find the model of traditional tourism governance format so that it can be used as a benchmark in the development of village tourism or sustainable hamlet tourism by re-arranging regulations based on local wisdom that support traditional tourism. Another objective is to evaluate and refine the implementation of village regulations that have been developed and implemented in the village tourism domain to determine the extent of their implications on improving the economy of people in tourist villages. This paper is authored using a qualitative approach with the orientation of literature study as an employed strategy in this study. The literature study is used in social research methodologies to trace historical data, as is found in this study. The results showed that the development of rural tourism is able to minimize the potential of urbanization from rural to urban society caused by the ability of local people to create economic activities based on tourism activities (tourism economy) in rural areas. The productive power of local potentials, including the potentials of rural areas, can be encouraged to grow and develop by utilizing the resources owned by the village, so that it can be an effective instrument in encouraging the development of socio-cultural and economic fields of rural communities. Furthermore, efforts will be encouraged to conserve and empower the potential of local culture and local wisdom values that tend to be threatened with extinction due to the heavily globalized currents that have entered rural areas. In the development of a tourist village, certain guidelines are needed so that the impact of the development of tourism activities in each rural area can be controlled. Keywords: tourism village; sustainable tourism development; economic empowerment; local wisdom.